2016
DOI: 10.1096/fj.201500019r
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of bacterial isochorismatase in the autophagic process induced byAcinetobacter baumanniiin mammalian cells

Abstract: A recent study reported that Acinetobacter baumannii could induce autophagy, but the recognition and clearance mechanism of intracytosolic A. baumannii in the autophagic process and the molecular mechanism of autophagy induced by the pathogen remains unknown. In this study, we first demonstrated that invading A. baumannii induced a complete, ubiquitin-mediated autophagic response that is dependent upon septins SEPT2 and SEPT9 in mammalian cells. We also demonstrated that autophagy induced by A. baumannii was B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 57 publications
1
40
2
Order By: Relevance
“…PhoP/PhoQ-HlyF pathway promoted the escape of ExPEC from phagolysosomes and entry into macrophage cytosol, our studies showed that ExPEC activated macroautophagy ( 57 , 60 ), since immunofluorescence labeling study demonstrated LC3-labeled ExPEC-containing autophagosome colocalized with Ub, a tag for antibacterial autophagy to decorate cytosolic bacteria ( 36 , 61 ). The colocalization of LC3 with wild-type ExPEC and the mutants suggested that PhoP/PhoQ-HlyF pathway might promote the formation of ExPEC-containing autophagosome during its survival in macrophages.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…PhoP/PhoQ-HlyF pathway promoted the escape of ExPEC from phagolysosomes and entry into macrophage cytosol, our studies showed that ExPEC activated macroautophagy ( 57 , 60 ), since immunofluorescence labeling study demonstrated LC3-labeled ExPEC-containing autophagosome colocalized with Ub, a tag for antibacterial autophagy to decorate cytosolic bacteria ( 36 , 61 ). The colocalization of LC3 with wild-type ExPEC and the mutants suggested that PhoP/PhoQ-HlyF pathway might promote the formation of ExPEC-containing autophagosome during its survival in macrophages.…”
Section: Discussionmentioning
confidence: 68%
“…During infection in the cytosol, pathogens induce and activate macroautophagy (microorganism-specific autophagy), which is a critical innate immune response pathway to target and degrade intracellular microorganisms ( 57 59 ). The autophagosomes (the typical double membrane compartments) are established during the autophagy, and the autophagy adaptor protein LC3 and p62 act as the typical markers for bacteria-containing autophagosome formation ( 57 , 60 ). Extensive works confirm that the LC3-I is gradually converted into LC3-II during the activated autophagy in response to bacterial infection, and autophagy-recruited LC3-II colocalizes with bacteria-containing autophagosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular bacterial killing assay was performed and evaluated by a gentamicin protection assay according to a previously published method (Wiedemann et al, 2012 ; Wang et al, 2016 ). The extracellular bacterial killing assay was performed and evaluated in accordance with a previously described method (Wang et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nicotinamidase/pyrazinamidase enzymes in Mycobacterium tuberculosis cleave the amide bond of pyrazinamide to produce the antibiotic pyrazinoic acid (Petrella et al ., ). Isochorismatases hydrolyze the activated vinyl ether bond of isochorismate in the shikimic acid pathway and function in phenazine production (Parsons et al ., ) and bacterial siderophore biosynthesis (Wang et al ., ). Other IHL superfamily subgroups perform more specialized functions, including the IHL streptothricin hydrolase in Streptomyces spp., which inactivates the antibiotic streptothricin via cleavage of the lactam ring (Hamano et al ., ).…”
Section: Introductionmentioning
confidence: 97%